Comparative historical analysis in the social sciences - Mahoney, James, 1968-; Rueschemeyer, Dietrich (Cambridge, U.K. ; New York : Cambridge University Press, 2009)
"Comparative Historical Analysis in the Social Sciences will serve as an invaluable resource for scholars in the field, and it will represent a challenge to many other social scientists - especially those who have raised skeptical concerns about comparative historical analysis in the past."--Jacket
Comparative-historical analysis: achievements and agendas / James Mahoney and Dietrich Rueschemeyer -- Comparative-historical analysis and knowledge accumulation in the study of revolutions / Jack A. Goldstone -- What we know about the development of social policy : comparative and historical research in comparative and historical perspective / Edwin Amenta -- Knowledge accumulation in comparative-historical research : the case of democracy and authoritarianism / James Mahoney -- Big, slow-moving, and ... invisible : macro-social processes in the study of comparative politics / Paul Pierson -- How institutions evolve : insights from comparative historical analysis / Kathleen Thelen -- Uses of network tools in comparative historical research / Roger V. Gould -- Periodization and preferences : reflections on purposive action in comparative historical social science / Ira Katznelson -- Can one or a few cases yield theoretical gains? / Dietrich Rueschemeyer -- Strategies of causal assessment in comparative historical analysis / James Mahoney -- Aligning ontology and methodology in comparative politics / Peter A. Hall -- Doubly engaged social science : the promise of comparative historical analysis / Theda Skocpol
Includes bibliographical references and index
Keywords: Social sciences -- Research -- Methodology